Constructing Good Citizenship Through Social Studies: Comparative Insights from Indonesia and Philippines - Kurniawan, Fahmi Kurniawan; Widiastuti, Anik; Wahyuni, Yuyun Sri (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
The massive developments of the times have encouraged the idea of protecting the younger generation from moral and character decay. To prevent this phenomenon, social studies (IPS) has emerged as an answer to concerns about moral and character decay. IPS is a field of study that aims to shape students into good citizens. This is implemented by all countries with their own policies. Indonesia and the Philippines are two countries that implement good citizenship as the goal of social studies education in their respective countries. Therefore, based on this background, the purpose of this article is to identify and compare the implementation of good citizenship in social studies education in Indonesia and the Philippines. The method used in writing this article is qualitative literature study research to analyze the comparison of the implementation of good citizenship in social studies education in Indonesia and Araling Panlipunan (AP) in the Philippines. The data was obtained through the stages of identification, data collection, analysis, interpretation, and refinement of the manuscript. The data was obtained through the stages of identification, data collection, analysis, interpretation, and refinement of the manuscript. The results of the study show that both countries implement good citizenship in social studies education, with Indonesia implementing it through the independent curriculum, while the Philippines implements it through the MATATAG Curriculum. The implementation of good citizenship in Indonesia is directed at the implementation of the Pancasila student profile, while in the Philippines it is directed at mastering civic engagement competencies.Keywords: Curicullum, Good citizenship, Social Studies, Araling Panlipunan.